Frequency of Device Use on Prosocial Behavior of Early Age Children 5-6 Years - Aidita Kirana; Kurniawati, Asih Budi; Sugiana (Universitas Pendidikan Ganesha, 2023)
The use of devices in early childhood has a time limit so that they have a good impact. The high frequency of device use among children will influence children's social behavior, especially prosocial behavior. This study aims to analyze the influence of frequency of device use on the prosocial behavior of children aged 5-6 years. This research uses ex-post facto quantitative research. The population in this study were parents (mothers) with children aged 5-6 years in PAUD institutions. This study used two-stage cluster sampling with a sample size of three sub-districts, one kindergarten for each with 59 parents (mothers). Data collection in this study used a questionnaire method with an instrument in the form of a statement sheet that parents (mothers) need to fill out to obtain data on the frequency of device use in children, children's prosocial behavior, and personal data on parents and children. The data obtained was then analyzed using a simple linear regression test processed with the help of SPSS. The data analysis results show an influence between the frequency of device use and the prosocial behavior of children aged 5-6 years. Apart from that, the correlation value shows a negative influence between the frequency of using devices and the prosocial behavior of children aged 5-6 years. This research implies that the frequency of using devices influences the prosocial behavior of children aged 5-6, meaning that the higher the frequency, the lower the child's prosocial behavior, and vice versa.